Criticism of Modernism as An Effort to Preserve the Sea in The Novel Mata dan Manusia Laut (Mata and The Sea Man) by Okky Madasari - Savitri, Adelia; Wahyuningtyas, Dwi (Universitas Airlangga, 2025)
This research focuses on the critique of modernism as an effort to preserve the ocean in Okky Madasari’s Mata dan Manusia Laut (Mata and the Sea Man). Modernism, which is considered the pinnacle of human civilization, is actually depicted in this novel as exploiting the sea. The purpose of this study is to reveal how sea preservation efforts in children’s novels are presented through issues of contradiction with modernism. By using a descriptive qualitative method based on Todorrov’s structuralism perspective, especially regarding point of view, the results of this study are that there is a binary opposition between the lives of the land people who are advanced in civilization and the sea people who are considered primitive, giving rise to a hierarchical relationship between subject and object. However, the Bajo tribe which maintains their local beliefs actually shows behavior in protecting and caring for the sea, in contrast to modernists who use technology to exploit the exoticism of the sea. Thus, it can be concluded that this novel contains character education values regarding: (1) the mindset of modernism must be positioned in balance with the values of local wisdom of the Indonesian people, (2) local beliefs that are considered irrational are actually capable of maintaining sea preservation.